2009
DOI: 10.1590/s1806-37132009001200002
|View full text |Cite
|
Sign up to set email alerts
|

Fatores de risco para visitas à emergência por exacerbações de asma em pacientes de um programa de controle da asma e rinite alérgica em Feira de Santana, BA

Abstract: Objective: To determine the risk factors for ER visits due to asthma exacerbations in patients monitored at a referral center. Methods: Prospective cohort study of 253 outpatients (children and adults) with asthma who were monitored for 12 months at the Referral Center of the Program for the Control of Asthma and Allergic Rhinitis in the city of Feira de Santana, Brazil. Results: Exacerbations were common, and 36.5% of the patients sought ER treatment within the twelve-month period. The risk factors for asthma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…In comparison with the patients with merely asthma, the patients with both asthma and concomitant allergic rhinitis recruit more medical surveillance and expenses that are estimated to be 2 fold. Therefore, evaluation of rhinitis symptoms would be done for amelioration of asthma [18,19]. This might be due to the lower resolution of airway obstruction [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with the patients with merely asthma, the patients with both asthma and concomitant allergic rhinitis recruit more medical surveillance and expenses that are estimated to be 2 fold. Therefore, evaluation of rhinitis symptoms would be done for amelioration of asthma [18,19]. This might be due to the lower resolution of airway obstruction [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…It results in a lower resolution of airway obstruction [12], increased frequency of asthma exacerbations and/or severity of asthma disease [26], higher probability of severe asthma [27] and uncontrolled asthma [12], increased school absence [28], increased visits to emergency rooms [12, 27, 29], more frequent hospitalization [29, 30], lower quality of life [17], higher healthcare cost [25, 29], and higher demand for health services [29]. …”
Section: Discussionmentioning
confidence: 99%
“…In a program for asthma and AR control, Brandão et al observed that a low education level, chronic rhinitis, and more severe asthma were risk factors for hospitalizations38 and emergency room visits due to increased asthma severity 37. Treatment for rhinitis was associated with a reduction in asthma severity.…”
Section: Discussionmentioning
confidence: 99%